THE GREEN REVOLUTION IN TOURISM: UNDERSTANDING ECOTOURISM'S ROLE IN A SUSTAINABLE FUTURE (Scientific Journal of Actuarial Finance and Accounting, 2024)
Ecotourism, a concept at the intersection of ecology and tourism, has emerged as a sustainable alternative to conventional travel. Rooted in principles of conservation, community empowerment, and cultural sensitivity, it addresses the environmental and societal challenges posed by mass tourism. This article examines the historical evolution of ecotourism, from its inception during the environmental movements of the 20th century to its recognition as a global strategy for sustainable development. Key principles, including environmental conservation, minimal impact, and education, are discussed alongside challenges such as over-tourism and greenwashing. The future of ecotourism is explored, emphasizing technological innovation, community-centric approaches, and regenerative practices as pathways to achieving ecological and societal harmony. By adhering to its core values, ecotourism holds the potential to drive meaningful change in the tourism industry while fostering global sustainability.